Manajemen Sains di Lembaga Pendidikan Islam - Riyanti, Triska; Irawan; Priatna, Tedi (CV Kalimasada Group, 2023)
This article discusses science management in Islamic Education Institutions with a case study of MAN 4 Garut. The purpose of this research is to find out and describe science laboratory management. The techniques used in data collection are observation, interview, and documentation study. The results of this study show several stages in science laboratory management to improve the quality of learning at MAN 4 Garut. First, the planning stage. Second, the organizing stage. Third, the administration stage. Fourth, the funding stage. The inhibiting factors of science management include many expired substances, thus inhibiting the practicum process. The solution to obstacles in science laboratory management to improve the quality of learning is the need for evaluation every semester in the management of science laboratories.